Size distribution of porbeagle (lamna nasus) inferred from a data - Mejuto-García, Jaime; Ramos-Cartelle, Ana; García-Cortés, Blanca; Fernández-Costa, José (2023)
A total of 5,136 size observations of porbeagle were recovered for the period 1987-2017. The GLM results explained very moderately the variability of the sizes considering three main factors, suggesting minor but significant differences in some cases especially for the year factor and non-significant differences in other factors depending on the analysis. The greatest differences in the standardized mean length between some zones were caused by some large fish of unidentified sex. The standardized mean length data for the northern zones showed stability throughout the time series, very stable range of mean values and very few differences between sexes. The size distribution for northern areas indicated an FL-overall mean of 158 cm. The size showed a normal distribution confirming that a small fraction of individuals of this stock/s is available in the oceanic areas where the North Atlantic fleet is regularly fishing and the fishes are not fully recruited to those areas and / or this fishing gear up to 160 cm. The data suggests that some individuals could sporadically reach some intertropical areas of the Atlantic